Conservatively Treated Incidental Aneurysm of the Distal Left Main Coronary Artery: Detection by Coronary Angiography and Noninvasive Followup Using Coronary Computed Tomography Angiography - Nina P. Hofmann; Hassan Abdel-Aty; Stefan Siebert; Hugo A. Katus; Grigorios Korosoglou (Case Reports in Cardiology)
Coronary artery aneurysms are relatively rare and commonly associated with significant coronary artery disease (CAD), inflammatory diseases (Kawasaki syndrome, infection), or iatrogenic complications. Herein, we report an unusual case of an incidental coronary aneurysm of the left main artery in a patient without specific clinical symptoms of myocardial ischemia or systemic inflammation and without angiographically significant CAD. Angiographic images are provided, acquired during cardiac catheterization, as well as coronary computed tomography angiography (CCTA) images obtained at 1 year of followup.